Gaps in the knowledge of human platelet lysate as a cell culture supplement for cell therapy: a joint publication from the AABB and the International Society for Cell & Gene Therapy - Bieback, Karen (Cytotherapy, 2019)
Fetal bovine serum (FBS) is used as a growth supplement in a wide range of cell culture applications for cell-based research and therapy. However, as a xenogenic product, FBS can potentially transmit prions and adventitious viruses as well as induce undesirable immunologic reactions. In addition, the use of bovine fetuses for FBS production raises concerns as society looks for ways to replace animal testing and reduce the use of animal products for scientific purposes, in particular for the manufacture of clinical products intended for human use. Until chemically defined media are available for these purposes, human platelet lysate (hPL) has been introduced as an attractive alternative for replacing FBS as a cell culture supplement. hPL is a human product that can be produced from outdated platelets avoiding ethical, medical and animal welfare concerns. An increasing number of studies demonstrate that hPL can promote cell growth similarly or even better than FBS in specific cell types. Due to increasing interest in hPL, the AABB and the International Society of Cell Therapy (ISCT) established a joint working group to address its potential. With this article, we aim to present an overview of hPL, identifying the gaps in information on how hPL is produced and tested and the barriers to its translational use in the production of clinical-grade cell therapy products.